Clinical and immunological characteristics of five patients with immune dysregulation, polyendocrinopathy, enteropathy, X-linked syndrome in China–expanding the atypical phenotypes - Huang, Yu; Fang, Shuyu; Zeng, Ting; Chen, Junjie; Yang, Lu; Sun, Gan; Dai, Rongxin; An, Yunfei; Tang, Xuemei; Dou, Ying; Zhao, Xiaodong; Zhou, Lina (Frontiers in Immunology, 2022)
Background: Immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome is rare disorder of the immune regulatory system caused by forkhead box P3 (FOXP3) mutations. Abnormal numbers or functions of regulatory T (Treg) cells account for the various autoimmune symptoms. We aimed to explore the molecular genetics and phenotypic spectra of atypical or late-onset IPEX patients in China. Methods: We analyzed the molecular, clinical and immune phenotype characteristics of five Chinese patients with FOXP3 mutations. Results: We summarize the molecular and phenotypic features of five patients with FOXP3 mutations, including two novel mutations. Four of the five patients displayed atypical phenotypes, and one developed immune-related peripheral neuropathy. Three of the five patients showed normal frequencies of Treg cells, but the proportions of subsets of Treg cells and CD4+ T cells were out of balance. Conclusions: Our report broadens the understanding of the clinical features of atypical IPEX syndrome. Our detailed analysis of the immunological characteristics of these patients enhances the understanding of the possible mechanisms underlying the clinical manifestations.